Blending Science with Fun Activities, Toys, and Games for Conceptual Understanding An Experimental Study - Verma, Ruchi; Satsangi, Mukta; Joshi, Meenakshi (JOURNAL OF INDIAN EDUCATION, 2023)
Quality of education is one of the most important concerns for a developing nation particularly with reference to science education. In this research study, fun activities, games, and toys were blended with different concept of science for generating interest and conceptual clarity in teaching-learning process of science at the Upper Primary Stage. The study was conducted with 116 learners organised during COVID 19 pandemic. It was observed that teaching-learning in science with games, activities and toys was significant in bringing change in better conceptual understanding of the subject and nurtured interest towards it. Such friendly and inclusive teaching-learning environment also resulted into active participation of learners. The study also opened new horizons in teaching-learning process for teachers as well. Traditional games, which have faded away from children’s life with time, were included in the study to bring them back in practice. Thus, such collaboration resulted in stimulating better conceptual understanding with development of social skills and behavioral aspects.